Work-Life Balance dalam Meningkatkan Kinerja Karyawan Milenial: Studi Kasus pada Universitas Ngudi Waluyo Ungaran - Setya Indah Isnawati; Irsal Fauzi; Faturahman Efendi; Silvina Widyastuti (Universitas 45 Surabaya, 2024)
This research was conducted to determine work-life balance in improving employee performance at Ngudi Waluyo University. The aim of this research is to understand the implementation of work-life balance for millennial employees, as well as adjusting the balance between personal and work life for millennial employees at Ngudi Waluyo University. The research method used is a qualitative method with a phenomenological approach. The number of research informants was 8 employee informants, consisting of lecturers, education staff, security guards, and office boys (OB). The research location is at Ngudi Waluyo University, Ungaran, Semarang Regency. The results of research from in-depth interviews found that the better the work-life balance that employees have, the more their performance will increase until they are able to achieve good quality. The advice aimed at millennial employees is to better understand time management in order to achieve work-life balance.